Exercice 1 : Développer chaque expression

B = 4(1 - 7y) + (4y - 5)(y - 1)

C = 3t(t + 1) + (5+ t)(t - 2)

D = (4k - 1)(9 + k) - 9k(10 - 3k)

E = (m + 2)(8 + 3m) - 2(1 - m)(m - 7)

Exercice 2 : Factoriser chaque expression

E = 10x² - 5x + 15

F = 4x² + 7x

G = 9x²(x + 1) + 6x(5 + x)

H = (11x - 3)² + (11x - 3)(5 + 9x)

1

Réponses

2012-12-05T15:43:05+01:00

exercice 1 :


B = 4(1 - 7y) + (4y - 5)(y - 1)

B = 4 - 28y + 4y² - 4y - 5y + 5

B = 4y² - 27y  + 9


C = 3t(t + 1) + (5+ t)(t - 2)

C = 3t² + 3 + 5t - 10 + t² - 2t

C = 4t² + 3t - 7


D = (4k - 1)(9 + k) - 9k(10 - 3k)

D = 36k + 4k² - 9 - k -90k + 27k²

D = 31k² - 55k - 9

 

E = (m + 2)(8 + 3m) - 2(1 - m)(m - 7)

E = 8m + 3m² + 16 + 6m -2 (1m - 7 - m² + 7m)

E = 26m + 5m² + 30